Enhanced ionic conductivity of an F−-assisted Na3Zr2Si2PO12 solid electrolyte for solid-state sodium batteries. Issue 25 (17th June 2020) - He, Shengnan; Xu, Youlong; Chen, Yanjun; Ma, Xiaoning
Abstract : F − -assisted Na3 Zr2 Si2 PO12 (NZSP) solid electrolyte with high ionic conductivity is promising as a solid electrolyte for solid-state sodium batteries. Abstract : Na3 Zr2 Si2 PO12 (NZSP) is considered to be one of the most promising solid electrolytes for solid-state sodium batteries. However, the low ionic conductivity of NZSP is one of the main challenges for its practical application. Herein, an F − assisting strategy to improve the ionic conductivity of NZSP is proposed. The F − assisting in NZSP electrolyte promotes the formation of a microstructure with large grains, low grain boundary concentration and high relative density, which is favorable to obtain high ionic conductivity. Consequently, the F − -assisted NZSP solid electrolyte exhibits a high ionic conductivity of 1.41 × 10 −3 S cm −1 at 27 °C, which is about six times that of the un-assisted NZSP electrolyte (2.32 × 10 −4 S cm −1 ). Moreover, the Na/Na3 V2 (PO4 )3 solid-state sodium battery with the F − -assisted NZSP electrolyte exhibits an excellent cyclability with 97.8% capacity retention (85.9 mA h g −1 ) after 100 cycles at 0.5C at 40 °C. This F − assisting strategy provides a new way for the development of other classes of ceramic solid electrolytes for solid-state batteries.